Analisis Restitusi Pajak Pertambahan Nilai Pada Kantor Pelayanan Pajak Pratama Jakarta Gambir Dua Periode 2005 Sampai Dengan 2008. - Ria Hartati (Journal Of Communication Education, 2019)
ABSTRACT Value Added Taxes (VAT) restitution is a refund process of VAT overpayment of tax payers, where the condition is the input tax is larger than output tax. However in practice, mostly it has misperception amongst tax payers and tax officers dealing with this VAT tax restitution and its impact to VAT revenue received by Gambir Pratama Tax Office.This research used descriptive analysis supported by quantitative and qualitative data as well as primary and secondary data. Interview was also utilized to gather some important information.The result of this research are as follows : First, the procedures to refund overpayment VAT can be done through two ways which are (1) for taxpayers who do not refund its VAT overpayment or (2) those who claim to refund VAT have to comply with all rules. Second the approved VAT restitution in 2007 had impacted to the level of VAT revenue received by Gambir Pratama Tax Offices.Keywords : Value Added Tax Restitutions, Tax Payers, Taxable Enterprises